Developing Effective Workforce via Industrial Based Project Supervision: A Case in Malaysian Technical and Vocational Education and Training Institutions - Ismail, Affero; Abiddin, Norhasni Zainal; Suwirta, Andi (EDUCARE, 2016)
ABSTRACT: The industrial based project has become a compulsory assessment for those who enrol in the TVET (Technical and Vocational Education and Training). The attributes in TVET require a student to be competent in the field to ensure it is comply with the industryâs demands of skilled workforce. During the industrial based project development, an effective supervision that involves the both student and supervisor are greatly needed. Thus, this paper will discuss the implementation of industrial based project in Malaysian TVET and explains the importance of effective supervision in project completion. The content is based on the literature review of previous researches from several sources, including documents, papers, and journals, which aimed to explore the best concept of effective supervision. The main concern is regarding the implementation of industrial based project in Malaysian TVET system, as well as clarifying the importance of effective supervision in studentsâ industrial based project completion. An EFA (Exploratory Factor Analysis) was conducted over 360 respondents to discover the factors in SIS (Supervisory Input Support). Then, CFA (Confirmatory Factor Analysis) was conducted to determine the AVE (Average Variance Extracted) and GoF (Goodness of Fit) model. The data regarding supervisory input is also discussed. It is hoped to provide a holistic view of effective supervision in developing skilled workforce. The ability to develop effective supervision in TVET should be catered in many ways which reflect the needs of students, for example by providing training to new supervisors. KEY WORDS: Industrial Based Project; Technical and Vocational Education and Training; Student; Skilled Workforce; Effective Supervision.Â Â Â Â About the Authors: Dr. Affero Ismail is a Lecturer at the Faculty of Technical and Vocational Education UTHM (Malaysia University of Tun Hussein Onn) in Johor, Malaysia. Assoc. Prof. Datoâ Dr. Norhasni Zainal Abiddin is a Lecturer at the Department of Professional Development and Continuing Education, Faculty of Education Studies UPM (University of Putra Malaysia) in Serdang, Selangor, Malaysia. Andi Suwirta, M.Hum. is a Lecturer at the Faculty of Social Studies Education UPI (Indonesia University of Education) in Bandung, West Java, Indonesia. Corresponding author is: nonieza99@gmail.com and suwirta.sahaja@upi.eduHow to cite this article? Ismail, Affero, Norhasni Zainal Abiddin & Andi Suwirta. (2016). âDeveloping Effective Workforce via Industrial Based Project Supervision: A Case in Malaysian Technical and Vocational Education and Training Institutionsâ in EDUCARE: International Journal for Educational Studies, Vol.8(2) February, pp.159-168. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (November 19, 2015); Revised (January 19, 2016); and Published (February 28, 2016).